Pengujian Toksisitas Akut Pada Obat Bahan Alam - Reubun, Yonathan Tri Atmodjo (Jurnal Ayurveda Medistra, 2020)
Toxicity tests need to be carried out on a drug product to be marketed. This initial test (screening test) is very important pharmacologically and toxicologically because it will be used for consideration of determining the dosage, the time span of administration and its application. Herbal medicine is a preparation of traditional medicine which until now its use is still needed by people in Indonesia. The toxicity testing method was chosen based on the Organization for Economic Co-operation and Development (OECD) guidelines. This method is a standard method that is recognized by many countries. Europe which is a member of the OECD. The main strengths of this method are the small amount of rodents used and the relatively fast testing time based on 3R principles. in a journal review, LD50 results were obtained in various plants, namely 0.2g / kg BW, 2g / kg BW, 3.91 g / kgBW, 3.91 g / kgBB, 4.9g / kgBW, 5g / kg BW, 16g / kg BW, and 22.41 g / kg BW. The conclusion from this test is the value of the toxic dose of herbal medicine is> 50-300 mg / kg bw as stated in Annex 2c: OECD / OCE.